2018
DOI: 10.3390/pathogens7020038
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Human Enteric Viruses, Protozoa, and Indicators of Pathogens in the Bagmati River, Nepal

Abstract: Quantification of waterborne pathogens in water sources is essential for alerting the community about health hazards. This study determined the presence of human enteric viruses and protozoa in the Bagmati River, Nepal, and detected fecal indicator bacteria (total coliforms, Escherichia coli, and Enterococcus spp.), human-fecal markers (human Bacteroidales and JC and BK polyomaviruses), and index viruses (tobacco mosaic virus and pepper mild mottle virus). During a one-year period between October 2015 and Sept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(56 citation statements)
references
References 52 publications
(67 reference statements)
1
54
0
1
Order By: Relevance
“…A study that was conducted in three sites of the Bagmati River (Sundarijal (upstream), Thapathali (midstream), and Chovar (downstream)) reported that the microbiological quality of the river water upstream was less degraded when compared to those at the other two sites [9]. Indicator bacteria, potential index viruses, and human-fecal markers were more frequently detected than protozoa and human enteric viruses at all three Bagmati River sites.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…A study that was conducted in three sites of the Bagmati River (Sundarijal (upstream), Thapathali (midstream), and Chovar (downstream)) reported that the microbiological quality of the river water upstream was less degraded when compared to those at the other two sites [9]. Indicator bacteria, potential index viruses, and human-fecal markers were more frequently detected than protozoa and human enteric viruses at all three Bagmati River sites.…”
Section: Introductionmentioning
confidence: 90%
“…As previously described [9], the Bagmati River water samples were collected every two months from the upstream, midstream, and downstream regions during a one-year period between November 2015 and September 2016, as shown in Figure 1. The sampling sites were selected based on population density in three regions of the Bagmati River basin, where the population density is lower in the upstream region when compared to the midstream and downstream regions, and also to observe the difference in bacterial community in start and end point of the Bagmati River flowing through the urban area of the Kathmandu Valley.…”
Section: Collection Of River Water Samples and Extraction Of Bacteriamentioning
confidence: 99%
See 1 more Smart Citation
“…74,76 Notably, HCoSV was recently detected using qPCR at relatively higher concentrations than observed in other environmental waters in the Bagmati River, Nepal, highlighting the importance of geographic variability in marker evaluation. 77 HCoSV may be a causative agent of waterborne viral disease; however, its variable specificity to wastewater (25-71%) across studies and presence in animal sources (pig) may limit its application for viral water quality monitoring. Notably, the recent detection of elevated HCoSV concentrations in environmental waters in Nepal points to a greater potential for application in specific geographic regions.…”
Section: Cosavirusmentioning
confidence: 99%
“…Studies showed that PMMoV and tobacco mosaic virus (TMV) are the most abundant and frequently detected viruses in sewage [15][16][17] . They are distributed globally and more abundant in environmental samples than human entric viruses, without any pronounced seasonal variation 18,19 . It may thus be beneficial to use PMMoV to evaluate the performance of drinking water and wastewater treatment processes 15,20 , although no studies have been conducted to date to evaluate the efficiency of reduction of TMV during wastewater treatment.…”
mentioning
confidence: 99%